MINIMUM LINEAR ARRANGEMENT OF THE TRANSITIVE ORIENTED, BIPARTITE GRAPHS - Sargsyan, H.E.; Markosyan, S.Ye. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
We study the minimum linear arrangement of the graphs (MINLA) on transitive oriented graphs. We prove that MINLA of transitive oriented graphs is NP-complete.